1986
DOI: 10.1152/jappl.1986.60.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of detraining on cardiovascular responses to exercise: role of blood volume

Abstract: In this study we determined whether the decline in exercise stroke volume (SV) observed when endurance-trained men stop training for a few weeks is associated with a reduced blood volume. Additionally, we determined the extent to which cardiovascular function could be restored in detrained individuals by expanding blood volume to a similar level as when trained. Maximal O2 uptake (VO2max) was determined, and cardiac output (CO2 rebreathing) was measured during upright cycling at 50-60% VO2max in eight enduranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 24 publications
(3 reference statements)
10
100
0
7
Order By: Relevance
“…Some authors compared aerobic values less than 60% of the highest theoretical value of HR during walking on TM and in DRW and there were no differences in the results (Gleim, & Nicholas, 1989;Whitley, & Schoene, 1987); however, according to our results, as other authors (Butts, Tucker, & Christine, 1991;Eyestone, Fellingham, George, & Fisher, 1993) above of 140 HR the differences among the values of HR are higher in the physical exercise developed on TM and in DRW. The results of this study are in accordance with values given by other authors who are among 10% (Butts, Tucker, & Christine, 1991), 14% (Coyle, Hemmert, & Coogan, 1984) and 16% (Eyestone, Fellingham, George, & Fisher, 1993).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Some authors compared aerobic values less than 60% of the highest theoretical value of HR during walking on TM and in DRW and there were no differences in the results (Gleim, & Nicholas, 1989;Whitley, & Schoene, 1987); however, according to our results, as other authors (Butts, Tucker, & Christine, 1991;Eyestone, Fellingham, George, & Fisher, 1993) above of 140 HR the differences among the values of HR are higher in the physical exercise developed on TM and in DRW. The results of this study are in accordance with values given by other authors who are among 10% (Butts, Tucker, & Christine, 1991), 14% (Coyle, Hemmert, & Coogan, 1984) and 16% (Eyestone, Fellingham, George, & Fisher, 1993).…”
Section: Resultssupporting
confidence: 93%
“…The maximum heart rate was 7.83% lower in water than for the standard laboratory ergometer test performed on land. Others have proposed values ranging from 10% (Butts et al, 1991), to 14% (Coyle et al, 1984), to 16% (Eyestone et al, 1993;Takeshima et al, 1997) for various populations of international level sportspersons. Although some authors found no differences in aerobic heart rate levels less than 60% of the theoretical maximum heart rate values between walking on land and in water (Gleim & Nicholas, 1989;McMurray, Fieselman, & Avery, 1988;Whitley & Schoene, 1987), this study like some others (Butts et al 1991;Eyestone et al 1993) found that above 140 bpm the differences in heart rate are greater between water-based and land-based exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our results show that iSDH activity and residuals were positively associated with capillarization (C/F and CAF) and likely with MCV, facilitating greater interstitial PO 2 , reflected by higher [O 2 HbMb] values. Surprisingly, both iSDH activity and residuals did not relate to RBC, [Hb], and Hct, possibly because those measures neglect differences in blood flow or blood volume (73). Secondly, [Mb] was not associated with iSDH activity or residuals (P = 0.16; P = 0.23, respectively).…”
Section: Physiology Of Sprinters: High Normalized Sprint Performance mentioning
confidence: 90%
“…The importance of hypovolemia is shown by inverse relationships between microgravity-induced plasma volume reduction and orthostatic tolerance [29]. Coyle et al [30] showed that the decline in SV and O 2 max and the V  increase in HR and TPR during upright exercise following a few weeks of inactivity (only sedentary daily routines and no training) in men who had been training intensely for several years, was largely due to a decline in blood volume. When blood volume was expanded by dextran solution, the reduction of cardiovascular function after a few weeks of detraining was minimal.…”
Section: Hypovolemia As Major Reason For Di-induced Cardiovascular Dementioning
confidence: 99%